Simbolisasi dalam Metode Numerik sebagai Representasi Konsep dan Prosedur - Fauzi Mulyatna; Wahyu Kusumaningtyas (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
The purpose of this research is to analyze the ability of interpret symbols in numerical methods. The extent of the interpretation at the level of procedure and calculation only, or its already at the level of understanding of the concepts represented by symbols with good and right way. This type of research is qualitative research. The data that obtained are analyzed in descriptive. The election of the subject based on purposive sampling technique, i.e. taking the subject with considerations/criteria 6 semester students who was taking the course numerical methods, critical and active in discussions. The subject is only drawn by 1 student, subsequently coded MN1.The material is focused in determining the approximate root of equation with the method of false position. The methods used to collect data in this research is the observation, tests and interviews. So, that the triangular used in this research is the triangular techniques. Conclusion based on the results of the research showed the new symbols to interpret NM1 limited calculation procedure only. NM1 considers, with the same symbol but different forms of counting operation, was a mistake. NM1 gives the wrong result of conclusion renders the procedure is only seen from the similarity to the symbol, not the views of the concept behind the use of the symbol.